قرطاجة والنوميد بين الصراع والتناغم - حمدي, خولة; بوحنيك, فاطمة الزهراء (جامعة الوادي - University of Eloued, 2022)
أجريت الدراسة الموسومة بقرطاجة والنوميد بين الصراع والتناغم 814-146 ق.م، سنة 2022 بجامعة الوادي، حيث تمحورت إشكالية الموضوع حول العلاقة القرطاجيةالنوميدية بين السلم والحرب ضمن الإطار الزماني المحدد، وقد هدفت الدراسة لكشف جميع مجالات التأثير القرطاجي فيما يخص الصراع المتمثل في المجال السياسي والتناغم الذي يشمل مختلف الجوانب الأخرى(الاقتصادية، الاجتماعية، العقائدية والثقافية) وقد خلصت الدراسة إلى أهم النتائج المتمثلة في: • ظهور العنصر البونيقي الناتج عن اختلاط الفينيقيين بالمغاربة. • عامل الاحتكاك بين الطرفين كان له الدور الكبير في ترك تأثيرات حضارية عديدةتشمل جميع المجالات. The study, tagged with Carthage and Numidian between conflict and harmony 814-146 BC. was conducted in 2022 at the University of el-oued, where the problematic of the topic centered on the Carthaginian Numidian relationship between peace and war within the specified time frame, and the study aimed to reveal all areas of Carthaginian influence regarding the conflict represented in the field Political and harmony that includes various other aspects (economic, social, ideological and cultural) The study concluded the most important results of The emergence of the Punic element resulting from the mixing of the Carthaginians with the Numidians. The friction factor between the two parties had a great role in leaving many cultural influences covering all fields
مذكرة ماستر تاريخ حضارات قديمة
Keywords: قرطاجة –نوميديا– الممالك النوميدية– الصراع - السلم; Carthage-Numidia – Numidian Kingdoms - conflict-peace